2023
DOI: 10.1177/02698811231182107
|View full text |Cite
|
Sign up to set email alerts
|

Baseline cognitive function predicts full remission of suicidal symptoms among patients with treatment-resistant depression and strong suicidal ideation after low-dose ketamine infusion

Abstract: Background: Whether pretreatment working memory and response inhibition function are associated with the rapid and sustained antisuicidal effect of low-dose ketamine among patients with treatment-resistant depression (TRD) and strong suicidal ideation is unclear. Methods: We enrolled 65 patients with TRD, comprising 33 who received a single infusion of 0.5 mg/kg ketamine and 32 who received a placebo infusion. The participants performed working memory and go/no-go tasks prior to infusion. We assessed suicidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The authors speculate that these changes could also be an indirect indicator of the plasticity changes induced by the drug. Lin et al (2023) report on their study about baseline cognitive function, which was shown to predict full remission of suicidal symptoms among patients with TRD and strong suicidal ideation after low-dose ketamine infusion. The authors note that whether pre-treatment working memory and response inhibition function are associated with the rapid and sustained antisuicidal effect of low-dose ketamine among patients with TRD and strong suicidal ideation is unclear.…”
mentioning
confidence: 99%
“…The authors speculate that these changes could also be an indirect indicator of the plasticity changes induced by the drug. Lin et al (2023) report on their study about baseline cognitive function, which was shown to predict full remission of suicidal symptoms among patients with TRD and strong suicidal ideation after low-dose ketamine infusion. The authors note that whether pre-treatment working memory and response inhibition function are associated with the rapid and sustained antisuicidal effect of low-dose ketamine among patients with TRD and strong suicidal ideation is unclear.…”
mentioning
confidence: 99%